Perception and Challenges of Blended Project-Based Learning Design Elements in Higher Education - Maureen, Irena Yolanita; Rusijono, Rusijono; Khotimah, Khusnul (Akademika, 2025)
Project-based learning (PBL) has gained traction in Indonesian higher education for its potential to foster critical thinking, collaboration, and creativity. However, its implementation remains limited in non-practical courses, where adaptation poses specific challenges. This study examines students’ perceptions of PBL implementation in a non-practical instructional system design course, focusing on four key elements: the collaborative process, student voice, technological aspects, and public presentation. The study involved 98 third-year students and two facilitators. Data were collected through a self-developed questionnaire and follow-up focus group discussions. Quantitative findings indicated generally positive perceptions, particularly regarding technological readiness and instructor support. Qualitative insights revealed ongoing challenges in group collaboration, role clarity, and the effectiveness of peer feedback, especially in blended learning settings. Students valued the structure and support provided by the instructor and expressed motivation when given creative space within defined parameters. The study emphasizes the importance of consistent scaffolding, structured interactions, and a supportive learning environment to facilitate the successful implementation of PBL in non-practical settings. Recommendations are offered to inform future course design and improve student engagement in similar contexts.